Health Information Systems and Organizational Support - Bambang Sunarko (Alliance of Health Activists (AloHA), 2019)
Almost all health institutions have taken part such as hospitals, health services, community health centers, health clinics, pharmacies, and so on. In its implementation, many health management information systems are found that do not run smoothly, many face various obstacles, some even fail so they cannot continue implementation. Organizational support has an important position in the implementation of health information systems, because these factors can directly influence actual system usage and prevent user resistance. If the supervisors and managers of information systems can provide active guidance and can exercise strict control, then the user will automatically be conditioned to always actively implement a health information system, so that the sustainability of the application of a health information system can be maintained. Keywords: Health information systems, Organizational support, User resistance